Preparation Laboratory Experiment for Medical Transportation with Drones – Switzerland - Mike KREY; Marc SANDMANN; Mathias KLINGLER; Gzim KRYEZIU (Communications of International Proceedings, 2022)
The healthcare sector in Switzerland is under big pressure concerning cost efficiency. Modern technologies such as drones aim for an improvement of this efficiency. In order to get an idea of the applicability of the use of drones in Healthcare in Switzerland, we conducted the paper “Use of Drones in Healthcare – Switzerland” beforehand. The essential take-aways from the paper are: 1. Drone technology can be used to deliver medical objects, telemedicine, emergencies and intra-hospitality. 2. The stakeholders´ attitude is more likely for the delivery and emergencies and less likely for the telemedicine and intra-hospitality drone. Based on the findings, a laboratory experiment for medical transportation with drones is conducted in the present paper. The laboratory experiment could not be executed due to a large gap between the identified requirements in this paper and the expectation from the drone manufacturer. Nevertheless, the preparation for a laboratory experiment is made and validated. Furthermore, a market analysis is conducted. This paper aims to give a first insight into the preconditions that have to be met before a pilot project can be executed, in order to have a successful pilot project.
Keywords: Drone; Healthcare; Case; Experiment.